Analisis Unforce Error Dan Dives Error Dalam Permainan Bulutangkis - Harmono, Bayu Akbar; Wahyono, Muhammad; Suryansah, Suryansah (Universitas Hamzanwadi, 2022)
This research was motivated by the badminton achievements of the students of PGRI University Surabaya. This achievement actually shows the shortcomings or weaknesses of the women's singles athletes at PGRI University Surabaya. Both in defending the attack or the attack ability that is not optimal, it results in ball errors such as unforce errors and diving errors. So that it produces a number for the opponent. The purpose of this research is to provide answers and scientific evidence about unforce error and dives error in the women's singles match for the students of Universitas PGRI Adi Buana Surabaya. This study uses a quantitative descriptive approach, with the subject of 6 female students at the University of PGRI Adi Buana Surabaya. This study analyzes unforce errors and dives errors in badminton. The results of the analysis of this study are: (1) Unforce error and dive error each have an effect of 28% for unforce error and 72% for dive error